Literary Ecology in Kongga Owose Folklore - S. Samsuddin (Journal of Indonesian Language Education and Literary, 2019)
Ecology and folklore are two different sides of life. Both have to do with different things. Ecology deals with the interrelationships between living things and the environment, such as land, water, plants and animals. While folklore is a part of life events in nature related to humans, nature, animals and plants that are passed down from generation to generation, from generation to generation in various shades of life and culture. The folklore of Kongga Owose implies three different stages of life, namely (1) the heyday of Kongga Owose, (2) the interim period, and (3) humans (Sorume people) fought against Kongga Owose.